Konsep Pendidikan Akhlak dalam Al-Qur’an: Kajian Tafsir Surat Al-Baqarah ayat 83 - Sudarto Sudarto; Dwi Noviani; Muhammad Amin Muttaqien (CV. ULIL ALBAB CORP, 2024)
Moral problems are lifelong problems of human presence on earth. History tells us that not a few civilizations collapsed due to moral deterioration. In Islamic studies, a separate terminology is found when faced with the discussion of morality, namely “akhlaq” which in some literature is also equated with personality or character. Apart from the exact equivalent of the word